Hubungan Antara Tekanan Darah Dengan Gangguan Emosional Tenaga Kerja Terpapar Tekanan Panas Di Unit Boiler PT. Indo Acidatama, Tbk. Kemiri, Kebakkramat, Karanganyar - Ambarwati, Devi Ayu (2016)
The Correlation Between Blood Pressure with Emotional Disorders of Labor which is Exposed to Heat Stress In Boiler Unit of PT. Indo Acidatama Tbk. Kemiri, Kebakkramat, Karanganyar. xiv + 90 + 15 Labor activities in the hot work environment causes the body releases heat. Body metabolic process that interact with the heat in the environment lead to labors experiencing heat stress. Hot environment resulting in increased body temperature therefore the blood pressure also increases. Increased blood pressure as a result of the hot environment can trigger the occurrence of emotional disorders. The purpose of this study was to determine the correlation between blood pressure with emotional disorders of labor which is exposed to heat stress in Boiler Unit of PT. Indo Acidatama Tbk. Kemiri, Kebakkramat, Karanganyar. This research method use observational analytic design with cross-sectional approach. The population in this study is a labors of Boiler Unit section wich are 30 people. The sampling technique used in this study is exhaustive sampling. Statistical test use the Spearman Correlation Test of Rho (ρ). Result of statistical test are obtained p-value of 0,019 or p ≤ 0,05 with Correlation Coefficient (r) about 0,425. It can be concluded that there is a significant correlation between blood pressure with emotional disorders of labor wich is exposed to heat stress in Boiler Unit of PT. Indo Acidatama Tbk. Kemiri, Kebakkramat, Karanganayar, wich is recommended when working in hot environments, labor should use appropiate personal protective equipment to keep the safety and health of labor at work